2016
DOI: 10.1515/bmt-2014-0181
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with imaging of the lower extremity arteries in an open 1.0 Tesla MRI system using the triggered angiography non-contrast-enhanced sequence (TRANCE) compared to digital subtraction angiography (DSA)

Abstract: Non-contrast-enhanced imaging of the lower limb arteries using a TRANCE-sequence in a 1.0 T open MRI system is feasible with the protocol presented; however, TRANCE tends to underestimate larger vessels and overestimate smaller vessels compared to DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…We cannot exclude that there was a possible slight over-estimation of the MRA derived vessel diameters as recently reported since our study context did not comprise the validation of vessel diameter measurements, e.g. macroscopic by pathology or visually by gold standard digital subtraction angiography [ 15 , 28 ]. In addition, we cannot exclude that also the degree of stenosis especially on the lower leg vessels was over-estimated by MRA in our study as reported before [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that there was a possible slight over-estimation of the MRA derived vessel diameters as recently reported since our study context did not comprise the validation of vessel diameter measurements, e.g. macroscopic by pathology or visually by gold standard digital subtraction angiography [ 15 , 28 ]. In addition, we cannot exclude that also the degree of stenosis especially on the lower leg vessels was over-estimated by MRA in our study as reported before [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although TRANCE-MRI has been used for diagnosing cranial diseases and mostly arterial diseases, there have been only a few applications of this technique in assessing venous pathology for the lower extremities. [ 11 , 12 , 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The triggered angiography non-contrast-enhanced (TRANCE) technique records differences in vascular signal intensity during the cardiac cycle for subsequent image subtraction and provides vascular images without using contrast agents. However, few clinical applications of this technique are known to exist for imaging the vascular pathology of the lower extremities [ 9 , 11 , 12 ]. In this study, we present our experience of using TRANCE-MRI and indicate its strengths and weaknesses in different cases of venous disease in the legs.…”
Section: Introductionmentioning
confidence: 99%
“…ECG-gating helps to adapt imaging times to different flow characteristics and, therefore, to optimize image quality faster. Although there is some related literature on non-contrast-enhanced MRA, most of them are associated with researchers using this technique to evaluate arterial diseases [ 26 , 27 , 28 , 29 ]. Our team has innovated the use of TRANCE-MRI for providing more valuable information for management of complicated lower venous diseases [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%